Education, sexualities and diversity in 19th century Germany: a study based on Karl Heinrich Ulrich (Research, Society and Development, 2022)
The study on canvas or in hand aims to contribute to filling gaps in the historiography of German homosexuality, building new perspectives for studies on gender and sexuality in Brazil. Methodologically, the study is based on a historical-descriptive literature review on the treatment of different forms of manifestation of (homo)sexualities through Karl Heirich Ulrichs. It is considered that Ulrich's studies on the condition of the subject "Urning" (homosexual) were responsible for the paradigm shift of the LSBTI movement, opposing the hegemonic scientific conceptions that saw the practice of homosexuality as "sodomy", an acquired addiction, aberration, abnormality and sin.